Adhesions to Mesh after Ventral Hernia Mesh Repair Are Detected by MRI but Are Not a Cause of Long Term Chronic Abdominal Pain - Odd Langbach; Stein Harald Holmedal; Ole Jacob Grandal; Ola Røkke (Gastroenterology Research and Practice)
Aim. The aim of the present study was to perform MRI in patients after ventral hernia mesh repair, in order to evaluate MRI’s ability to detect intra-abdominal adhesions. Materials and Methods. Single-center long term follow-up study of 155 patients operated for ventral hernia with laparoscopic (LVHR) or open mesh repair (OVHR), including analyzing medical records, clinical investigation with patient-reported pain (VAS-scale), and MRI. MRI was performed in 124 patients: 114 patients (74%) after follow-up, and 10 patients referred for late complaints after ventral mesh repair. To verify the MRI-diagnosis of adhesions, laparoscopy was performed after MRI in a cohort of 20 patients. Results. MRI detected adhesions between bowel and abdominal wall/mesh in 60% of the patients and mesh shrinkage in 20–50%. Adhesions were demonstrated to all types of meshes after both LVHR and OVHR with a sensitivity of 70%, specificity of 75%, positive predictive value of 78%, and negative predictive value of 67%. Independent predictors for formation of adhesions were mesh area as determined by MRI and Charlson index. The presence of adhesions was not associated with more pain. Conclusion. MRI can detect adhesions between bowel and abdominal wall in a fair reliable way. Adhesions are formed both after open and laparoscopic hernia mesh repair and are not associated with chronic pain.